2003
DOI: 10.1023/a:1023735821900
|View full text |Cite
|
Sign up to set email alerts
|

Participation in trauma research: Is there evidence of harm?

Abstract: Few studies have examined the impact of trauma research participation upon trauma survivors. Empirical data regarding reactions to research participation would be very useful to address the question of whether it is harmful for trauma survivors to participate in trauma studies. We examined participant reactions to different trauma assessment procedures in domestic violence (N = 260), rape (N = 108), and physical assault (N = 62) samples. Results indicated that participation was very well tolerated by the vast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
191
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(213 citation statements)
references
References 16 publications
17
191
1
4
Order By: Relevance
“…If the risks of longitudinal studies are high, ethical considerations may preclude this type of research. Griffin et al [14] examined participant reactions to different trauma assessment procedures for domestic violence, rape and physical assault and found that trauma survivors in fact viewed research studies as interesting and valuable experiences. Survivors might also recognize studies as opportunities to communicate their experiences and attitudes to others.…”
Section: Discussionmentioning
confidence: 99%
“…If the risks of longitudinal studies are high, ethical considerations may preclude this type of research. Griffin et al [14] examined participant reactions to different trauma assessment procedures for domestic violence, rape and physical assault and found that trauma survivors in fact viewed research studies as interesting and valuable experiences. Survivors might also recognize studies as opportunities to communicate their experiences and attitudes to others.…”
Section: Discussionmentioning
confidence: 99%
“…Malpass, et al (2015) for example use the term 'symbolic violence' (Bourdieu, 1996) There is a concern that contributing to DVA research is associated with increased risk of violence if the perpetrators come to know about it. However, it has been suggested that this concern to some extent has been based in assumptions, anecdotal evidence (Griffin, Resick, Waldrop, & Mechanic, 2003;Kuyper, de Wit, Adam, & Woertman, 2012) or "…worst case scenarios of research atrocities" (Sikweyiya & Jewkes, 2012, p. 1). On the contrary, such participation can be beneficial and cathartic (Edwards, Kearns, Calhoun, & Gidycz, 2009;Sikweyiya & Jewkes, 2012) and may prove empowering (Downes, Kelly, & Westmarland, 2014).…”
Section: Participant's Safetymentioning
confidence: 99%
“…We believe that our finding that minimal risk applies to community-based observational studies of IPV will extend to studies of other sensitive topics in the general population. In their study of research impact on survivors of traumatic experiences, Griffin, Resick, Waldrop, and Mechanic (2003) found that survivors regarded their participation in research as interesting and helpful. Future studies on partner violence and other sensitive topics are needed to replicate and extend our findings and those of Griffin and colleagues.…”
Section: Limitations and Future Researchmentioning
confidence: 99%